2008
DOI: 10.1093/aob/mcn069
|View full text |Cite
|
Sign up to set email alerts
|

Carry-over of Differential Salt Tolerance in Plants Grown from Dimorphic Seeds of Suaeda splendens

Abstract: The seeds most likely to germinate at high salinity in the Mediterranean summer (brown ones) retain a requirement for higher salinity as seedlings that might be of adaptive value. On the other hand, black seeds, which are likely to delay germination until lower salinity prevails, produce seedlings that are less sensitive to salinity. It is not clear why performance at low salinity, later in the life cycle, might have been sacrificed by the brown seeds, to achieve higher fitness at the germination stage under h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 35 publications
5
29
0
2
Order By: Relevance
“…Such ontogenetic niche shifts have been documented in other taxa (e.g., Dalling et al 2001, Miriti 2006, Molofsky & Augspurger 1992, Parrish & Bazzaz 1985, Redondo-Gomez et al 2008, Song et al 2008, Thomson et al 1996. Such niche shifts can potentially restrict the conditions under which a taxon can persist; conditions that permit survival of both stages must be present within a given location, and this is a situation that is likely to be less common than the occurrence of conditions that permit the survival of only one stage.…”
Section: Constraints Of Ontogeny Revisited: Comparing the Germinationmentioning
confidence: 97%
See 1 more Smart Citation
“…Such ontogenetic niche shifts have been documented in other taxa (e.g., Dalling et al 2001, Miriti 2006, Molofsky & Augspurger 1992, Parrish & Bazzaz 1985, Redondo-Gomez et al 2008, Song et al 2008, Thomson et al 1996. Such niche shifts can potentially restrict the conditions under which a taxon can persist; conditions that permit survival of both stages must be present within a given location, and this is a situation that is likely to be less common than the occurrence of conditions that permit the survival of only one stage.…”
Section: Constraints Of Ontogeny Revisited: Comparing the Germinationmentioning
confidence: 97%
“…Seasonal or successional changes in vegetation cover, competitive environment, or abiotic factors such as water or nutrient availability often change over the course of the life span of individuals, as does the organisms' exposure to particular environmental factors over the course of development (Bazzaz 1991). When the environment itself changes during ontogeny in a manner that matches the niche, ontogenetic niche shifts could actually be advantageous (Anderson et al 2009, Redondo-Gomez et al 2008.…”
Section: Constraints Of Ontogeny Revisited: Comparing the Germinationmentioning
confidence: 99%
“…It is 25.5 ± 0. 86 16,265 in S. monoica and 10,175 in S. nudiflora. The pollen-ovule ratio is equal to the pollen out per anther due to oneovuled flowers in all the three species.…”
Section: Floral Biologymentioning
confidence: 97%
“…Chapman (1947) also reported three principal varieties, vulgaris, macrocarpa and flexilis, based on growth habit and seed size. Redondo- Gomez et al (2008) reported that several Suaeda species exhibit seed dimorphism and produce both brown and black seeds simultaneously and these varying colorations reflect two different dormancy and germination strategies for survival in saline habitats. Ponnamperuma (1984) explained that occurrence of different growth forms reflect different soil conditions present in high and low salt marshes due to difference in aeration levels.…”
Section: Derris Trifoliatamentioning
confidence: 99%
“…It is possible that a stable quencher was formed in presence of NaCl and that it did not decay during the dark adaptation period before measurement. Alternatively, it could be concluded as well that under low NaCl conditions plants are more prone to photoinhibition, through damage to PSII reaction centres (Redondo-Gómez et al 2010). Redondo-Gómez et al (2007 and found that absence of salt represented an environmental stress factor for Atriplex portulacoides and Suaeda splendens, respectively, since there was a marked midday reduction in F v /F m at 0 mM NaCl.…”
mentioning
confidence: 99%